Street edge subdivision: Structuring ground floor interfaces to stimulate pedestrian visual engagement. (July 2022) - Simpson, James; Freeth, Megan; Simpson, Kimberley Jayne; Thwaites, Kevin
There have been numerous attempts to identify what makes the ground floor interfaces of street edges engaging for pedestrians. Their subdivision has often been highlighted as important, predominantly, in line with functions along their length. However, the effect of subdivision on street edge engagement is yet to be empirically tested. We use mobile eye-tracking to systematically examine where and for how long pedestrians visually engage ground floors in relation to their subdivision. We consider three scales of subdivision: morphologically defined plinths (different building ground floors), territorially defined segments (different areas of territorial ownership) and spatially defined micro-segments (different spaces separated by pillars and partitions). Results show that segments dominate ground floor visual engagement, with micro-segments also having a significant influence. Plinths were shown to have no direct effect upon such engagement. We subsequently use these findings to show how subdivision should be approached by design decision-makers when seeking to actively encourage pedestrian engagement with ground floors along street edges.